Pharmacological blockage of the CXCR4-CXCL12 axis in endometriosis leads to contrasting effects in proliferation, migration, and invasion†. Issue 1 (17th November 2017) - Ruiz, Abigail; Ruiz, Lynnette; Colón-Caraballo, Mariano; Torres-Collazo, Bryan J; Monteiro, Janice B; Bayona, Manuel; Fazleabas, Asgerally T; Flores, Idhaliz
Abstract: High levels of inflammatory factors including chemokines have been reported in peritoneal fluid and blood of women with endometriosis. CXCL12 mediates its action by interaction with its specific receptor, CXCR4, reported to be elevated in human endometriosis lesions and in the rat model of endometriosis. Activation of the CXCR4-CXCL12 axis increases cell proliferation, migration, and invasion of cancer cells. To obtain insights into the CXCR4 expression profile in lesions and endometrium, as well as functionality of the CXCR4-CXCL12 axis in endometriosis, we analyzed the expression of CXCR4 in tissues on a human tissue array and studied CXCL12-mediated activation of proliferation, invasion, and migration in vitro. We observed differences in levels of nuclear CXCR4 expression among lesion types, being higher in ovarian lesions. Endometriotic cell lines (12Z) showed higher levels of CXCR4, proliferative and migratory potential, and AKT phosphorylation/kinase activity compared to untreated control cells (endometrial epithelial cells). CXCL12 and endometriotic stromal cell-enriched media increased proliferation of non-endometriotic epithelial cells. CXCL12 caused a significant increase in 12Z cell invasion but had no effect on migration; AMD3100, a CXCR4-specific inhibitor, significantly increased invasion of 12Z cells but decreased their migration. However, treatment with CXCL12 plus AMD3100 significantly decreased invasion and migration of 12Z cells. In conclusion, the CXCR4-CXCL12 axis is functional in endometriosis cells, but the expression of CXCR4 varies among lesions. CXCL12 promoted proliferation, migration, and invasion of endometriotic cells, while inducing AKT phosphorylation and activity, but pharmacologically blocking this axis in the absence of the ligand induced their invasiveness. Summary Sentence: CXCL12 treatment of endometriotic cells promoted their proliferation, migration, and invasion, while inducing AKT phosphorylation and activity, but pharmacologically blocking this axis in the absence of the ligand increased their invasion capacity.